State Court Statistics, 2009 ([Verlag nicht ermittelbar], 2012)
This data collection provides comparable measures of state appellate and trial court caseloads by type of case for the 50 states, the District of Columbia, and Puerto Rico. Court caseloads are tabulated according to generic reporting categories developed by the Court Statistics Project (CSP) Committee of the Conference of State Court Administrators. These categories describe differences in the unit of count and the point of count when compiling each court's caseload. Major areas of investigation include (1) case filings in state appellate and trial courts, (2) case processing and dispositions in state appellate and trial courts, and (3) appellate opinions. The trial caseload consists of civil, domestic relations, criminal, juvenile, and traffic violation cases. The appellate caseload consists of appeal by right, appeal by permission, death penalty, and original proceeding/other appellate matter cases.